PENGARUH MEDIA TERHADAP EFEKTIVITAS PEMBELAJARAN PRAKTIKUM BIOKIMIA - Eddy Sulistyowati; Retno Arianingrum; Togu Gultom; Das Salirawati (MAJALAH ILMIAH PEMBELAJARAN, 2006)
The objectivity of this research is to determine media that effective to studying in biochemistry practical work to improve student achievement.The sample of this research is all students of biochemistry practical work at odd semester in 2003/2004 in Chemistry Department in Faculty of Mathematics and Natural Science, at Yogyakarta State University. The student’s number was 28 people. The research was carried out using 3 media, i.e. Over Head Transparent presented by Over Head projector (OHP) at carbohydrate topic; Power Point presented by LCD projector at protein topic, and Audio-Visual presented by LCD projector at enzyme topic. The instruments of this research are observation sheet, pre-test and post-test, and evaluation questionnaire. The increase of post-test to pre-test was evaluated using t-test. The analyzed of observation data was carried out by qualitative descriptive using calculation percentage continued by qualitative analyzed. The mean of observation data was analyzed by ANAVA-A test followed by LSDT test. The data of evaluation questionnaire was calculated as percentage of student choice at this questionnaire.The result of observation data showed that there was the increasing in practical work skilled using OHT, Power Point, and Audio Visual media. There were 18.16 (very low), 36.39 (medium); and 49.31 (very high) respectively. The ANAVA-A test and LSDT indicated that there was significant difference between three score of the practical work skilled with three different media at three topics. The result of pre-test and post-test showed that there was the increasing score for all topics. The great increasing was enzyme topic when using Audio-visual media. The t-test indicated that there was the differentia of the increase score at three topics. The evaluation questionnaire showed that Audio-Visual media presented by LCD was effective